Bullismo femminile: presentazione della ricerca quantitativa di un'indagine nazionale mixed-method - Federico Batini; Irene Dora Maria Scierri; Francesco Vittori (LED Edizioni Universitarie, 2023)
FEMALE BULLYING: PRESENTATION OF THE QUANTITATIVE RESEARCH OF A NATIONAL MIXED-METHOD INVESTIGATION Abstract Due to its seriousness and prevalence, bullying is a crucial topic for educational research, also in order to adopt appropriate educational strategies to prevent and tackle it. One of the possible avenues of investigation is the adoption of a gender perspective. In fact, bullying is often studied with a universalistic approach, despite the fact that research shows the presence of peculiarities that can be associated, albeit not exclusively, with different genders. The national project «Female bullying at school. An intersectional mixedmethod investigation» aims to better understand bullying among girls by adopting a gender and intersectional perspective. This contribution presents the quantitative part of the research. The outcomes regarding the incidence and characteristics of bullying will be discussed and the gender differences that emerged will be explored. The results confirm the relevance of the phenomenon and highlight the peculiar gaze of girls, providing support for the usefulness of adopting a gender perspective in the study of bullying.